Local lexical intrusions in english dailies: A comparison of Malaysian, Singaporean and Pakistani newspapers - David, M.K.; Kuang, C.H.; Shaikh, Q.A. (2008)
This research examines data from English newspapers in Malaysia, Singapore and Pakistan in order to determine the extent of nativization of local varieties of English. The papers examined are 'The New Straits Times' and 'The Star' from Malaysia, 'The Straits Times', 'Sunday Times', 'Today' and 'The New Paper' from Singapore 'The Nation' and 'The News' from Pakistan. The borrowing and assimilation of a large number lexical items are analysed and categorized. The categorization across the countries will be discussed. Such informed knowledge truly makes English an Asian language.